High intensity interval training exercise increases dopamine D2 levels and modulates brain dopamine signaling - Tyler, John; Podaras, Madeline; Richardson, Brittany; Roeder, Nicole; Hammond, Nikki; Hamilton, John; Blum, Kenneth; Gold, Mark; Baron, David A.; Thanos, Panayotis K. (Frontiers in Public Health, 2023)
Background Previous research has outlined the health benefits of exercise including its therapeutic potential for substance use disorders (SUD). These data have already been utilized and it is now common to find exercise as part of SUD treatment and relapse prevention programs. However, we need to better understand different exercise regimens and determine which would be the most beneficial for SUDs. Recently, high intensity interval training (HIIT) has gained attention in comparison with aerobic and resistance exercise. Little is known regarding the neurobiological mechanisms of HIIT, including its effects on dopamine signaling and receptor levels in the brain. The present study examined the effects of chronic HIIT exercise on dopamine signaling as measured by dopamine type 1-like receptor (D1R)-like, dopamine type 2-like receptor (D2R)-like, and tyrosine hydroxylase (TH) quantification in the brains of male and female rats as measured by [3H] SCH 23390 and [3H] spiperone autoradiography, and TH-immunoreactive optical density values. Methods Rats were separated in two groups: sedentary and HIIT exercise. Exercise was on a treadmill for 30 min daily (10 3 min cycles) for six weeks with progressive speed increased up to 0.8 mph (21.5 m/min). Results Results showed for D2R-like binding, a significant effect across the ventral caudate putamen (V CPU) between sexes, such that mean D2R-like binding was 14% greater for males than females. In the nucleus accumbens shell (Nac Shell), the HIIT Exercise rats showed 16% greater D2R-like binding as compared to the sedentary rats. No significant effects of HIIT exercise were found across groups for brain D1R-like binding levels or TH expression. Conclusion These results suggest that HIIT exercise can modulate dopamine signaling by way of increased D2R. These findings support the premise that HIIT exercise plays an important role in dopamine signaling and, may provide a potential mechanism for how HIIT exercise can impact the brain and behavior.